Partition, correlation, and natural bioconcentration of iron, manganese, and zinc in cacao trees - Bahia, Bismark Lopes; Santana, Thays Moura; Medauar, Caique Carvalho; Pinto, Flavia Conceicao; Soares, Mariana Bomfim [UNESP]; Santana Reis, Marcia Eduarda; Santos, Carolina Amorim; Jesus, Raildo Mota; Souza Junior, Jose Olimpio (Taylor & Francis Inc, 2021)
The aim of this study was to evaluate the variability, partition, and correlation of Fe, Mn, and Zn in the leaves and fruit components (pod husk, pulp, tegument, and cotyledons) of cacao trees. These contents were also correlated with chemical attributes of the soils in regions classified as humid (H), humid to sub-humid (SH), and sub-humid to dry (SD) in the South Bahia, Brazil. Soils samples were collected, along with leaves and fruits from the PH16 clone of the cacao tree, for analysis of Fe, Mn, and Zn. Descriptive statistics and Pearson's correlation were applied, as well as Shapiro Wilk's normality test and Tukey's test for comparison of the climate regions. The accumulation order for Fe and Zn in the fruit components was tegument > pod husk > leaf > cotyledons; and for Mn the order was pod husk > leaf > tegument > cotyledons. The increase in hydric restriction, from the most humid region to the driest, causes natural bioconcentration of Fe, Mn, and Zn in the fruit components used to produce food (cotyledons and pulp). The Mn contents in the leaf can be used as indicators of its accumulation in the cotyledon and cacao pulp.
Keywords: cacao nibs; cacao pulp; micronutrients; mineral nutrition; Theobroma cacao L